VARIABILITY IN CENOZOIC SEDIMENTATION ALONG THE CONTINENTAL RISE OF THE BELLINGSHAUSEN SEA, WEST ANTARCTICA - Scheuer C.; Gohl K.; Larter R.D.; Rebesco M.; Udintsev G. (My University, 2006)
Seismic reflection profiles, bathymetric and magnetic data collected along and across the continental margin of the Bellingshausen Sea provide new constraints and interpretations of the oceanic basement structure and Cenozoic glacial history of West Antarctica. Evidence for tectonic boundaries that lie perpendicular to the margin has been identified on the basis of one previously unpublished along-slope multichannel seismic reflection profile. By combining several magnetic data sets, we determined basement ages and verified the positions of possible fracture zones, enabling us to improve previous tectonic and stratigraphic models. We establish three main sediment units on the basis of one seismic along-slope profile and by correlation to the continental shelf via one cross-slope profile. We interpret a lowermost unit, Be3 (older then 9.6 Ma), as representing a long period of slow accumulation of mainly turbiditic sediments. Unit Be2 (from about 9.6 to 5.3 Ma) may represent a period of short-lived ice advances on the continental shelf. The uppermost unit, Be1 (from about 5.3 Ma to present), apparently consists of rapidly deposited terrigenous sediment that we interpret as having been transported to the shelf edge by frequent advances of grounded ice. Listric faults are observed in Be1 and indicate sediment instability due to interactions between different depositional processes. Correlation of the sediment classification scheme with the continental rise of the western Antarctic Peninsula shows obvious differences in sediment depositional patterns. We estimate a very high sedimentation rate for Unit Be1 (up to 295 m/my) which points to an increase in glacial sediment supply due to major glacial outlets that flowed to nearby parts of the shelf edge in Pliocene and Quaternary times. This is in contrast to the situation at the adjacent Antarctic Peninsular margin and many other parts of the continental rise around Antarctica. © 2006 Elsevier B.V. All rights reserved.
Keywords: BELLINGSHAUSEN SEA; CONTINENTAL MARGIN; CONTINENTAL RISE; MIOCENE; SEDIMENT DRIFTS; SEDIMENTATION; SEISMIC REFLECTION; WEST ANTARCTICA; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен